Prevalence of active HCV infection and genotypic distribution among the general population of district Mardan, Pakistan - Ullah,N. (2023)
Abstract Hepatitis C virus (HCV) is the serious global public health burden of liver disease. Approximately 170 million people in the world are infected with (HCV). In Pakistan, where the disease has high occurrence rate. The present study envisages an up-to-date prevalence of HCV and genotypic distribution in the general population of Mardan District, Khyber Pakhtunkhwa (KP), Pakistan. The blood samples from 6,538 individuals including 3,263 males and 3,275 females were analyzed for hepatitis C surface antigen by Immuno-chromatographic test (ICT), Enzyme-linked immunosorbent assay (ELISA), and reverse transcription-polymerase chain reaction (PCR). It was found that 396 (12.13%) out of 3263 individuals contained antibodies in their blood against HCV, while among the different age groups, the highest incidences of HCV antibodies were found in the 31-40 age group (11.01%). The ICT positive samples were further screened by nested PCR to determine the existence of active HCV-RNA. It was identified that 7.11% (3263) of the total population (6538) tested was positive, among which the 461 (14.07%) females possessed antibodies in their blood against HCV. Our data showed total HCV infection in the investigated population was 5.78%. Higher percentage of HCV prevalence was detected in males than females in the age group 31-40 and 41-50. To compare the prevalence of HCV genotypes age-wise in male and female genotype 3a was found most prevalent genotype followed by 1a, 2a and 3b, respectively.